Teknik Elisitasi Kebutuhan Perangkat Lunak: Literatur Review - Ari Cahaya Puspitaningrum; Endah Septa Sintiya (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The selection of software requirements elicitation techniques is very important for organizations as the first step in the software development process. This study is motivated by the existence of problems, where the organization does not understand the type of software being developed, so it is difficult to determine the right need elicitation technique. In this study, a literature review was used by collecting existing studies. Used 17 studies related to the discussion of elicitation techniques used. This study aims to review previous studies so as to produce recommendations for software requirements elicitation techniques. Based on the study, it can be concluded that interview, prototyping and JAD are most often used in software projects. In addition, for the small-medium scale software projects, more use of interviews, JAD, and ERD-based specifications. Meanwhile, the large-scale software projects involve more stakeholders with elicitation techniques such as group discussions, interviews, and parallel discussions to find joint solutions.